Design and Construction of the Al-Qur'an Education Park at the At-Taqwa Mosque, Demak: Improving Religious Education Infrastructure in Kebon Batur Village - Narendra, Alfa; Sutarto, Agung; Siswoyo, Mohammad Pujo; Haryadi, Bambang (Universitas Negeri Semarang, 2024)
This community service project aims to design the Al-Qur'an Education Park (TPQ) at the At-Taqwa Mosque, Kebon Batur Village, Demak, to provide facilities that support religious education for local children. The At-Taqwa Mosque was chosen as the location because it plays an important role in religious development in the area, but currently still has limited facilities to support adequate TPQ activities. Through a participatory approach involving the local community, discussions, field observations, and designs based on educational building standards were carried out. The result of this activity is a safe, functional, and environmentally friendly TPQ design, which is expected to be a guideline for the development of sustainable religious education facilities.